A method for design 3 blade type and testing optimum cavitation of tailing thai boat - Noosomton, Jaruphant; Charoensuk, Jarruwat (My University, 2014)
This paper presents a method for optimized cavitation of 3-blade type ship propeller. Cavitation flow is investigated around ship propellers experimentally. Testing of two different types of new model propellers and local type propellers are performed in this study. A 3-blades, skew angle 20 degree, developed area 50 and 35, so called model A (B3-20-50), and model B (B3-20-35) respectively, and finally a local type propeller popular used among local fisherman are compared. The results are presented in characteristic curves are related pictures. Finally, the results ate discussed, Model A and B is investigated based on existing experimental results. In addition, model C is a comparison validation to non-optimum for used to shallow-fishery and tailing Thai boat. A practical method was achieved by combining a vortex lattice lifting method and lifting surface method. The optimum circulation distribution yielding the maximum lift-to-torque ratio was computed for given thrust and chord lengths along the radius of the propeller by dividing the blade into a number of panels extending from hub to tip. The radial distribution of bound circulation could be computed by a set of vortex elements that have constant strengths. The cavitation phenomenon is appear to monograph of model A and B the better model C (local type), such as, the cavitation prediction on a hydrofoil is carried out in both steady and unsteady states. The results show good agreement in comparison with available experimental data. Furthermore, the propeller cavitation breakdown is well reproduced in the proceeding. The overall values suggest that the present approach is a practicable tool for predicting probable cavitation on propellers during design processes.
Keywords: Cavitation number; Optimum ship propeller; Propeller design